HUBUNGAN CARA BELAJAR DENGAN HASIL BELAJAR MATA DIKLAT STATIKA SISWA KELAS X TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 PARIAMAN - 294-300 , Edo Kurniawan (Universitas Negeri Padang, 2014)
ABSTRACT This research is correlation research that aimed to reveal the relationship between students’ learning method and study results of 84 students in class X construction architecthure technique SMKN 1 Pariaman on year of school 2012/2013. This research is using purposive sampling technique, and sample acquired is 40 students. Data which is used in this research is primary and secondary data. Primary data is collected by questionnaire about student’s learning method, while student’s result is acquired from teacher of statistic subject. From the analysis, it shows that there is a relationship between students’ learning method and study results of 84 students in class X construction architecthure technique SMKN 1 Pariaman on year of school 2012/2013. It is appeared in t-test which is thit (3.352) ³ ttable (2.025). keyword : learning method, study result